13=k-1

Simple and best practice solution for 13=k-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13=k-1 equation:



13=k-1
We move all terms to the left:
13-(k-1)=0
We get rid of parentheses
-k+1+13=0
We add all the numbers together, and all the variables
-1k+14=0
We move all terms containing k to the left, all other terms to the right
-k=-14
k=-14/-1
k=+14

See similar equations:

| 12m=-72 | | 30z+1=301 | | x-(81/3)=70 | | 6^(x)=84 | | 4x-2x-8=14 | | a15-262=a5-12 | | 3.5(-x+14)=43.5 | | 10=2m-70 | | 3x+12+6x+6=180 | | -83=k-17 | | 5d-6=94 | | -6=-2(3x+5) | | -3(x-5/83=3/16 | | 11x−13x−5x−–18x=11 | | 5f+15=-15 | | –9u+8=–10u | | y-17=-83 | | 26=3x-46 | | –9h+9=–10h | | -n^+32=4n | | 5.9=-z | | -4b-1=-25 | | 100+66x=71x | | u+8=-18 | | 5k-2=-27 | | 6x+6=158-10x | | 7(-6y+8-9=) | | 19+2x=5+4x | | 8+4g=-8 | | 11t+8=52 | | 2x+2x-7+2=4+2(x-5)+2x | | 50+7x=42+15x |

Equations solver categories